A study of the efficiency of the plant (Nile flower) in removing iron and copper from polluted water bodies in Iraq (Journal of the College of Basic Education, 2022)
Contamination of the aquatic environment by toxic metal ions is a serious problem , phytoremidation is one of the wastewater treatment methods using plant based system for removing contaminants from various sources[ 1] . The aim of this research is to study the efficiency of (Eichhornia Crassipas) in removing Iron and copper ions from polluted wastewater.The removal rates of ions are varied according to the type and concentration of the ions in the media .The average removal rates of copper is higher than iron in separate ions solutions ,but the matching between Copper and Iron in the mixed ions solutions is small due to the similarity in ions sizes and charges .The BioConcentration Factor (B.C.F.) of ions is increased according to ions concentrations in the media and growing time of the plant .